Ultrasound-guided high-intensity focused ultrasound ablation for uterine arteriovenous fistula: a case series - Fang Li; Hua Tao; Jing Chen; Li Wang; Yini Wei; Xiajuan Wu; Yu Zhang; Dingyuan Zeng (International Journal of Hyperthermia)
Purpose To evaluate the efficacy and safety of high-intensity focused ultrasound (HIFU) ablation in the treatment of uterine arteriovenous fistula (UAVF).Materials and methods This case series included three patients diagnosed with acquired UAVF. All patients underwent routine laboratory tests, electrocardiography (ECG), chest X-ray, ultrasound, and pelvic contrast-enhanced magnetic resonance imaging (MRI). HIFU treatment was performed under sedation and analgesia using a Model JC Focused Ultrasound Tumor Therapeutic System (made by Chongqing Haifu Medical Technology Co. Ltd., China) with a B mode ultrasound device for treatment guidance. The treatment time, sonication power, sonication time, and complications were recorded. Follow-up evaluations were scheduled at 1-, 3-, 6-, and 12-month to assess symptom improvement and evaluate the post-treatment imaging.Results All patients completed HIFU treatment in a single session without any major complication. All patients complained of mild lower abdominal and sacrococcygeal pain. Typically, no special treatment is required. Following HIFU treatment, there was a significant relief in clinical symptoms, particularly abnormal uterine bleeding. Ultrasound examinations conducted one month after the treatment revealed a notable reduction in the volume of the lesion, ranging from 57% to 100%. Moreover, the efficacy and safety of HIFU treatment remained consistent during the 12-month follow-up period.Conclusion HIFU ablation appears to be an effective and safe treatment modality for UAVF. It provides a noninvasive approach with favorable clinical outcomes.